Assessing the Effectiveness of One-Hour Instruction Sessions After Hurricane Sandy: A Comparison Study of English 101 Students. Issue 1 (2nd April 2016) - White, Scott; Cheng, Hong
ABSTRACT: The purpose of this article is to chronicle and discuss a unique research opportunity at LaGuardia Community College when Hurricane Sandy caused a week of class cancelations, including library instruction sessions for ENG101 students. Librarians took advantage of the natural sample, paired with randomly selected classes that had previously attended library instruction sessions and tested students' basic research skills by using pre and post surveys. This project serves as a benchmark for assessing students' learning effectiveness in one-hour instruction sessions. The article presents an instruction assessment research project by using pre- and post-session surveys. Students who took a library one-hour instruction session performed significantly better than students who did not on tested learning outcomes. The article concludes that assessment results provide solid data in students' improvement and teaching efficacy. Results may also help library instructors make decisions about assessing and improving library instruction. Due to an unexpected circumstance, the library faculty researchers took advantage of a natural research sample and compared canceled classes with classes that had library instruction sessions on several basic research skills.